2011
DOI: 10.1007/s10165-011-0542-4
|View full text |Cite
|
Sign up to set email alerts
|

Behçet’s disease and genes within the major histocompatibility complex region

Abstract: The role of genetic background in the development of Behçet's disease (BD) is best reflected by the strong association between HLA-B*51 and BD that has been demonstrated across various ethnic groups. The contributions made by other HLA or non-HLA genes to disease susceptibility have been suggested by the results of a number of gene association studies, although the true associations between the genes located within the major histocompatibility complex (MHC) region and BD have often been doubted due to the poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
0
8
0
1
Order By: Relevance
“…To date, available evidence has suggested that tumor necrosis factor (TNF) inhibitors may be effective for treatment of leg ulcers. [ 5 , 6 ] Mesenchymal stem cells (MSCs), mainly isolated from bone marrow and some other sources such as umbilical cord blood, possess unlimited self-renewal and pluripotential capacity. [ 7 ] Several studies have documented the immunosuppressive and anti-inflammatory effect that MSC may exhibit in different diseases.…”
Section: Introductionmentioning
confidence: 99%
“…To date, available evidence has suggested that tumor necrosis factor (TNF) inhibitors may be effective for treatment of leg ulcers. [ 5 , 6 ] Mesenchymal stem cells (MSCs), mainly isolated from bone marrow and some other sources such as umbilical cord blood, possess unlimited self-renewal and pluripotential capacity. [ 7 ] Several studies have documented the immunosuppressive and anti-inflammatory effect that MSC may exhibit in different diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of the gene in this novel susceptibility locus may make a great contribution to more understanding of the pathogenesis of BD, as it may explain the expression of the disease in HLA-B*51 negative individuals, and also the fact that not all HLA-B*51 positive individuals develop the disease. It is likely that the expression of genes other than HLA-B*51, serves as an additional risk factor of developing BD [13].…”
Section: Susceptible Genesmentioning
confidence: 99%
“…In humans, a significant correlation was observed between neutrophil hyper function and HLA-B*51 positivity, regardless of the presence of BD. Thus, it appears that HLA-B*51 might be responsible, at least in part, for neutrophil hyperactivity in BD, and the possession of HLA-B*51 is not sufficient to induce clinical disease, and additional genetic or environmental factors are required to trigger disease development [13].…”
Section: Hlamentioning
confidence: 99%
See 1 more Smart Citation
“… 40 Besides HLA-B51 molecules, SNPs in TNF and IL-10 genes have been implicated in susceptibility to BD. 24 , 41 – 43 However, the results are inconsistent and variations are found among several ethnic populations. So in this study, the association of five polymorphisms in TNF-α , - β , and IL-10 genes with BD susceptibility risk in Saudi patients was evaluated.…”
Section: Introductionmentioning
confidence: 99%